Chemical composition of pequi essential oil (Caryocar brasiliense) and nematicidal activity in the control of Meloidogyne javanica - Alves Marques, Átila; Nogueira de Sousa, Bruno; Nascimento Guimarães, Nathália; de Moura Martins, Carla; Vieira da Silva, Rodrigo (Revista Ceres, 2023)
The phytonematodes seriously harm plants worldwide, reducing agricultural productivity, especially root-knot nematodes, genus Meloidogyne. An alternative form of control for this pathogen is the use of essential oils, which have a complex mixture of compounds with potential nematicidal activity. The objective of this work was to identify the chemical compounds present in the essential oil of pequi and to verify the efficiency of the oil in the control of Meloidogyne javanica. The identification of chemical compounds was performed by comparing the mass spectra obtained with the spectra present in the equipment library, Nist08. Eighty-second stage juveniles (J2) were incubated in the following treatments: control 0 (2 mL of distilled water) 2, 4, 8 and 16 mg L-1 of pequi essential oil (PEO). The results obtained in the experiment were significant, with a high percentage of mortality of J2 in the treatment T5 (16 mg L-1) of 82% and T3 (4 mg L-1) 66%, respectively. Among the compounds identified, 58.3% are esters, highlight for ethyl hexanoate, and 25.0% are monoterpenes, and all are nematicidal compounds. Pequi essential oil has the potential to be used in the control of M. javanica.